Polyphenols and ω-3 PUFAs: Beneficial Outcomes to Obesity and Its Related Metabolic Diseases - Siroma, Thais Keiko; Machate, David Johane; Zorgetto-Pinheiro, Verônica Assalin; Figueiredo, Priscila Silva; Marcelino, Gabriela; Hiane, Priscila Aiko; Bogo, Danielle; Pott, Arnildo; Cury, Elenir Rose Jardim; Guimarães, Rita de Cássia Avellaneda; Vilela, Marcelo Luiz Brandão; Ferreira, Rosângela dos Santos; et al. (Frontiers in Nutrition, 2022)
Obesity is associated with the leading causes of death in the worldwide. On the other hand, the intake of vegetables, fruits and fish is related to the reduction of obesity and other metabolic syndromes. This review aims to highlight the role of ingestion of polyphenols and omega-3 polyunsaturated fatty acids (ω-3 PUFAs) in reducing obesity and related metabolic diseases (RMDs). The consumption of vegetables, fish and by-products rich in polyphenols and α-linolenic acid (ALA), as well as oils rich in eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are associated with a decrease in obesity and its RMDs in consumers. Furthermore, we discussed the adequate amount of extracts, powder, polyphenols, ω-3 PUFAs administrated in animal models and human subjects, and the relevant outcomes obtained. Thus, we appeal to the research institutions and departments of the Ministries of Health in each country to develop a food education joint project to help schools, businesses and families with the aim of reducing obesity and other metabolic diseases.